1998
DOI: 10.1093/humrep/13.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term low-dose mifepristone on reproductive function in women

Abstract: Low-dose antiprogestin administration has been proposed as a new contraceptive modality to interference with endometrial receptivity without disturbing ovarian function. The effects of 1 mg/day mifepristone for 150 days on the menstrual cycle were assessed in 21 surgically sterilized women. The aim was to study each woman for one control cycle and during months 1, 3 and 5 of treatment. Ovulation, endometrial thickness, serum oestradiol and progesterone, urinary luteinizing hormone, endometrial morphology and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…Previously published studies (20)(21)(22) have shown that low-dose mifepristone might be an effective contraceptive regimen with few side effects. For example, a single-dose (2 mg/kg body weight) administration of mifepristone led to inhibition of implantation without affecting serum steroid hormonal profiles or menstrual cycles in rhesus monkeys (21), and daily administration of mifepristone (1 mg/day) blocked endometrial development while allowing biphasic ovarian cycles and regular bleeding in women (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published studies (20)(21)(22) have shown that low-dose mifepristone might be an effective contraceptive regimen with few side effects. For example, a single-dose (2 mg/kg body weight) administration of mifepristone led to inhibition of implantation without affecting serum steroid hormonal profiles or menstrual cycles in rhesus monkeys (21), and daily administration of mifepristone (1 mg/day) blocked endometrial development while allowing biphasic ovarian cycles and regular bleeding in women (22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single-dose (2 mg/kg body weight) administration of mifepristone led to inhibition of implantation without affecting serum steroid hormonal profiles or menstrual cycles in rhesus monkeys (21), and daily administration of mifepristone (1 mg/day) blocked endometrial development while allowing biphasic ovarian cycles and regular bleeding in women (22). When mifepristone was administered at a concentration of 1 mg/day, the steady plasma level of mifepristone was found to be 65 nmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a direct role of PR in human and rat ovarian function has been supported in recent years by the demonstration that [1] the antiprogestin RU486 inhibits ovulation in the human (7) and [2] LH is the primary signal for rupture of preovulatory ovarian follicles and induces a transient expression of PR mRNA for both protein isoforms in granulosa cells isolated from rat preovulatory follicles (7)(8)(9).…”
Section: Classic Progesterone Receptors and Ovarian Functionmentioning
confidence: 99%
“…We sought to assess the effects of H 2 O 2 , NAC, RU486, and CDB on the YHES cell proliferation, since their effects on endometrial cell growth have been well documented either in vivo or in vitro [25,26,[54][55][56][57][58][59][60] . Treatment with H 2 O 2 at low concentrations of 1 and 10 M increased cell proliferation by 18 and 22%, respectively, while treatment with a higher concentration of 100 M of H 2 O 2 induced inhibition of proliferation ( fig.…”
Section: Effects Of H 2 O 2 Nac Ru486 and Cdb On Cell Proliferationmentioning
confidence: 99%